Pengaruh Kepuasan Kerja terhadap Turnover Intention dengan Komitmen Organisasional sebagai Variabel Mediasi: (Studi pada PT BPR Sukawati Pancakanti, Gianyar) - Putu Putri Belinda; Made Surya Putra (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study examines the effect of job satisfaction on turnover intention through the mediating role of organizational commitment among employees of PT BPR Sukawati Pancakanti, Gianyar. Human resource management plays a crucial role in maintaining employee loyalty and reducing turnover intention, particularly in the banking sector, where service quality depends heavily on employee performance and commitment. This research employed a quantitative approach involving 155 employees selected using a saturated non-probability sampling technique. Data were collected through interviews and questionnaires distributed via Google Forms and analyzed using path analysis. The findings reveal that job satisfaction has a significant negative effect on turnover intention, indicating that employees with higher job satisfaction are less likely to leave the organization. Job satisfaction also has a significant positive effect on organizational commitment, while organizational commitment significantly reduces turnover intention. Furthermore, organizational commitment partially and complementarily mediates the relationship between job satisfaction and turnover intention. These findings support the traditional turnover theory, which explains that employees’ intention to leave develops through sequential psychological evaluations in which job satisfaction strengthens organizational commitment before influencing turnover intention. Practically, PT BPR Sukawati Pancakanti is encouraged to improve employee satisfaction through fair compensation, appropriate workload distribution, and a supportive work environment. Strengthening employees’ sense of responsibility and commitment is expected to reduce turnover intention, enhance productivity, and improve overall organizational performance.